Nano-Glass Ceramics : Processing, Properties and Applications - Marghussian, Vahak (Micro & nano technologies., 2015)
Nano-Glass Ceramics: Processing, Properties and Applications provides comprehensive coverage of synthesis and processing methods, properties and applications of the most important types of nano-glass ceramics, from a unique material science perspective. Emphasis is placed on the experimental and practical aspects of the subject while covering the theoretical and practical aspects and presenting, numerous examples and details of experimental methods. In the discussing the many varied applications of nano-glass ceramics, consideration is given to both, the fields of applications in which the materials are firmly established and the fields where great promise exists for their future exploitation. The methods of investigation adopted by researchers in the various stages of synthesis, nucleation, processing and characterization of glass ceramics are discussed with a focus on the more novel methods and the state of the art in developing nanostructured glass ceramics.